The reliability of use of WhatsApp in type 1 and type 2 pediatric supracondylar fractures - (:unkn) unknown (TURKISH JOINT DISEASES FOUNDATION, 2019)
Objectives: This study aims to evaluate the reliability of the assessment of radiological X-ray images of traumatic injuries in the elbows of children using WhatsApp application, compared to true-size images on a Picture Archiving and Communication System (PACS) screen. Patients and methods: Between November 2017 and March 2018, X-ray images of a total of 90 pediatric patients (53 males, 37 females; mean age 6.2 years; range, 2 to 10 years) with an elbow injury were retrospectively evaluated. The images were captured and sent to three orthopedic surgeons via the WhatsApp instant messaging application on an iPhone 7S smartphone. Observers were asked to diagnose and classify for each case over their personal smartphones. The three observers independently assessed the images with a seven-day interval. Following one-week interval, revaluation was conducted using the PACS. Intra-and interobserver reliability were calculated by Cohen Kappa statistics. Results: There was a good agreement between the first and second evaluations by the physicians via WhatsApp (k=0.74). The intraobserver reliability was very good (k=0.8), moderate (k=0.55), and good (k=0.67). There was no significant difference in the intra- and interobserver reliability between the groups. Conclusion: Using WhatsApp for consulting is a reliable method which can be used in the emergency setting for decision-making. Using WhatsApp can improve the efficacy of medical assessment and reduce waiting time in emergency admissions, although this method is not a substitution for evaluation of the images using computer-based PACS.
Keywords: Fracture; pediatric elbow; smartphone; supracondylar fracture; WhatsApp; SMARTPHONES; COMMUNICATION; ORTHOPEDICS